Endogenous modulation of compatibility effects: an Investigation into the temporal dynamics. Issue 2 (7th February 2019) - Machado, Liana; Devine, Amy
ABSTRACT: Compatibility effects (CEs) arise when multiple stimuli fall within the visual field, providing an indication of stimulus processing. Previous research demonstrated that exogenous factors (e.g., luminance) influence the magnitude of CEs and their time course. The current research investigated the influence of endogenous factors. We used a flanker paradigm with a variable temporal delay (SOA) between a flanker and a subsequent central stimulus appearing. To manipulate endogenous factors, we required responses to the flanker on either half or all of the trials. The results indicate that increasing the task relevance of the flanker strengthened the initial positive CE (measured at short SOAs), consistent with past findings related to exogenous factors. However, at longer SOAs, the CE did not reverse into a negative CE, which stands against findings related to exogenous factors. These results indicate that CEs are subject to endogenous modulation, but the temporal dynamics do not mimic exogenous modulation.